Avaliação de métodos de decomposição de chocolate e determinação de metais por ICP-OES e ICP-MS - Marques Junior, Jucelino Medeiros (2014)
In this work, was evaluated the main methods of sample preparation reported in the literature for decomposition of chocolate and, in addition, was proposed the decomposition by microwave induced combustion (MIC) for further determination of Cd, Co, Cr, Ni and Pb by inductively coupled plasma mass spectrometry (ICP-MS) and pneumatic nebulization with inductively coupled plasma optical emission spectrometry (PN-ICP-OES) and ultrasonic nebulization (USN-ICP-OES). MAWD was splitted in 4 ways: (MAWD-1) 300 mg of sample + 6 mL concentrated HNO3 + 1 mL of H2O2 (30%), (MAWD-2) 300 mg of sample + 6 mL concentrated HNO3, (MAWD-3) 500 mg of ground sample (powder) + concentrated HNO3 + 1 mL of H2O2 (30%) and (MAWD-4) 300 mg of sample + 4 mL concentrated HNO3 + 2 mL concentrated HCl. Moreover, the decomposition was performed in a closed system using single reaction chamber (SRC MAWD). In the MIC was evaluated the mass of the sample and the HNO3 concentration as absorption solution. The procedure MAWD-3 presented agreement of values for all analytes after determination by ICP-MS with other procedures MAWD and SRC MAWD. Besides, the residual carbon content (RCC) after decomposition by MAWD-3 was 1.4 ± 0.1% without significant difference with the other procedures MAWD. Thus, the decomposition of chocolate by MAWD could be used up to 500 mg of sample without grinding. In the decomposition of chocolate by dry ashing was observed losses for Cd and in the decomposition in open vessels the RCC was 14%. In the MIC was possible to decompose up to 500 mg of chocolate with 7 mol L-1 HNO3 as absorption solution and the RCC value was 0.20 ± 0.02%, six fold lower compared to the MAWD procedures. There was agreement in the results for Cr and Ni obtained by PN-ICP-OES compared with the results obtained by ICP-MS for almost all preparation methods evaluated. The values for Cd and Pb were below the limit of detection (LD) by PN-ICP-OES. In the decomposition of certified reference material (CRM) of whole milk powder by MAWD-2 and determination by ICP-MS were observed agreement in the range of 107, 104 and 91% for Co, Cr and Pb, respectively, and agreement in the range of 97 and 95% for Co and Pb, respectively, using CRM non-fat milk. The LDs obtained for Cd, Co and Cr by USN-ICP-OES showed a significant improvement when compared with the LDs obtained by PN-ICP-OES. For Pb there was an improvement up to ten fold in the detection limits for USN-ICP-MS when compared with PN-ICP-OES. However, the determination of Ni was not possible for USN-ICP-OES. Thus, MAWD-3 and MIC 7 mol L-1 methods were satisfactory for decomposing up to 500 mg of chocolate, decomposition times lower than open systems and the possibility of determination Cd, Co, Cr and Pb by ICP-MS or USN-ICP-OES.